PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN DISIPLIN KERJA GURU TERHADAP KINERJA GURU PADA SEKOLAH DASAR NEGERI - Eliyah, Eliyah; Tamam, Badrud (Universitas Wiralodra, 2019)
The purpose of this study is the magnitude of the influence between the leadership style of the principal and the work discipline of the teacher both individually and jointly on the performance of the teacher in the Public Elementary School in the Haurgeulis District of Indramayu Regency. This research was conducted to find an analysis of the relationship between school principal supervision and work climate with the motivation of elementary school teachers working in Kertasemaya Subdistrict, Indramayu Regency with correlational and regression techniques. The type of research used is quantitative, namely research based on the calculation of numbers or statistics of a variable to be studied separately and then connected. Based on the results of the study it can be concluded (1) there is a positive and significant influence of the principal's leadership style (X1) on Teacher's performance (Y) in Public Elementary Schools in the Haurgeulis District of Indramayu Regency. The magnitude of the influence of the principal's leadership style (X1) on Teacher performance (Y) in Public Elementary Schools in the District of Haurgeulis in Indramayu Regency was 6.84% and the rest was influenced by teacher discipline variables and other variables not examined in this study. (2) There is a positive and significant influence of teacher work discipline (X2) on Teacher performance (Y) of Public Elementary Schools in Haurgeulis District, Indramayu Regency. The magnitude of the influence of teacher work discipline (X2) on the performance of Teachers (Y) of Public Elementary Schools in the District of Haurgeulis in Indramayu Regency amounted to the remaining 10.5% influenced by the principal leadership style variables and other variables not examined in this study. (3) There is a positive and significant influence of the principal's leadership style (X1) and teacher work discipline (X2) together on the performance of Teachers (Y) of Public Elementary Schools in the Haurgeulis District of Indramayu Regency. The magnitude of the influence of the principal's leadership style (X1) on the performance of Teachers (Y) of Public Elementary Schools in the District of Haurgeulis in Indramayu Regency amounted to the remaining 10.5% influenced by other variables not examined in this study.